The Relationship Between Maternal Obesity with Pregnancy-Associated Hypothyroidism, Fetal Health, and Pregnancy Outcomes - Lourance Al Hadid; Omymah Z. Al-Rajabi; Marwa Al Barmawi; Ahmad Yahya AL-Sagarat (Journal of Holistic Nursing and Midwifery)
Introduction: The prevalence of obesity is increasing worldwide, especially among pregnant women. Maternal obesity is a serious risk factor during pregnancy associated with pregnancyrelated complications for the mother and her child. Objective: This study aimed to estimate the prevalence of Jordanian pregnant women who are overweight or obese. The relationship between high body mass index and selected obstetrical conditions was also investigated. Materials and Methods: A descriptive, correlational, cross-sectional design was used on a purposive convenience sample of 411 pregnant women in Jordan. Results were obtained through structured interviews, antenatal routine lab tests, physical measurements (height and weight), body mass index (BMI), thyroid function tests (free thyroxine [FT4] and 2e [TSH]), and Edinburgh postnatal depression scale. Descriptive statistics, including means, standard deviation, and inferential statistics, such as Pearson correlation, t-test, and ANOVA, were used to describe and examine the relationship among the study variables. Results: Based on the results, 58.4% of the participants had one to four pregnancies, and 54.5% had at least one abortion. Based on their weight before pregnancy, there was a high frequency of overweight (29.7%) and obesity (25%) among pregnant women. High maternal BMI for the mother is correlated significantly with pregnancy complications and offspring neurocognitive impairments. Additionally, maternal obesity is a risk factor for hypothyroidism. BMI was correlated with hypothyroidism (r=0.141, P=0.004), fetal distress (r=0.217, P=0.0001), postnatal depression (r=0.161, P=0.0001), and preterm labor (r=0.115, P=0.020). The thyroid function tests and thyroid stimulating hormone levels were correlated with maternal and fetal conditions, such as infertility, fetal death, hemorrhage, and cerebral palsy among children. Conclusion: High BMI associated with old age is a critical factor related to many maternal and infant health conditions. Repeated pregnancy failures, fetal health conditions, and maternal complications, including hypothyroidism, can be associated with maternal obesity. Healthcare providers should raise awareness among mothers and care providers on the serious conditions associated with obesity.